A revision of the genus Jucancistrocerus Blüthgen, 1938 from China, with review of three related genera (Hymenoptera: Vespidae: Eumeninae) - Li, Ting-Jing; Bai, Yue; Chen, Bin (Zootaxa, 2022)
In this paper, the genus Jucancistrocerus Blüthgen 1938 from China is systematically reviewed, with the first description of the female of J. (Eremodynerus) chotanensis (Blüthgen, 1942). Meanwhile, three related genera Eustenancistrocerus Blüthgen, Stenancistrocerus de Saussure and Tachyancistrocerus Giordani Soika are briefly reviewed, of which Eustenancistrocerus and Tachyancistrocerus are newly recorded from China. A total of nine species of these four genera from China are illustrated as follows: J. (Eremodynerus) atrofasciatus (Morawitz, 1885), J. (E.) chotanensis (Blüthgen, 1942), J. (J.) tachkensis, J. (J.) alashanicus Kurzenko, 1977, J. (J.) angustifrons (Kostylev, 1940), E. (Eustenancistrocerus) askhabadensis (Morawitz, 1885), E. (Parastenancistrocerus) amadanensis amadanensis (de Saussure, 1855), S. (Paratropancistrocerus) transcaspicus (Kostylev, 1934), and T. schmidti (Kokujev, 1912). In addition, a key to the above species is compiled.